2023
DOI: 10.1021/acsomega.3c01252
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Antiproliferative Activity and Apoptosis Induction of New Nickel(II) Complexes Encompassing Carbazole Ligands

Abstract: To attest the effectiveness of nickel complexes as anticancer drug candidates with minimum side effects, the present investigation describes the facile synthesis and anticancer activities of nickel(II) complexes enriched with three derivatives of carbazolone-based benzhydrazone ligands(L) having a [Ni(L) 2 ] composition. Analytical and spectral techniques were used to characterize the synthesized Ni(II) complexes. The single-crystal X-ray diffraction performed for complex 4 confirmed the square planar geometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated that presence of a methoxy group (–OCH 3 ) in some molecules can significantly increase biological activity, particularly antiproliferative performance. 42,46,72,73 Unsubstituted Ni II -L 1 (with R = H) did not present antiproliferative activity in any of the tested cell lines (IC 50 > 100 μM). In contrast, its methoxy-containing derivative Ni II -L 2 (with R = –OCH 3 ) was the most potent anticancer agent (IC 50 = 3.4–11.3 μM).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous studies have demonstrated that presence of a methoxy group (–OCH 3 ) in some molecules can significantly increase biological activity, particularly antiproliferative performance. 42,46,72,73 Unsubstituted Ni II -L 1 (with R = H) did not present antiproliferative activity in any of the tested cell lines (IC 50 > 100 μM). In contrast, its methoxy-containing derivative Ni II -L 2 (with R = –OCH 3 ) was the most potent anticancer agent (IC 50 = 3.4–11.3 μM).…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, it was not possible to establish a clear correlation when including the methoxy group, in agreement with previous reports. 42,46,72,73 More salophen derivatives are required to assess the role played by substituents (R = H or -OCH 3 ) in the aromatic rings and further studies to examine the pathways of action through which these kinds of complexes act.…”
Section: Cell Viability Studymentioning
confidence: 99%
See 2 more Smart Citations